Sources and methods in the history of sexuality
1 online resource.
Keywords: Sources and Methods in the History of Sexuality outlines some of the challenges of retracing sexual acts, identities, and desires in the past, and shows how historians have responded to these methodological challenges with ingenuity and creativity. The volume acknowledges that the history of sexuality poses particularly interesting challenges in relation to sources due the peculiar nature of sexuality. On one hand, sexuality is frequently hidden and private, its practices often unknown, denied, and evaded, its desires fleeting or obsessive, its reality confused or illuminated by fantasy; yet on the other, sexuality consistently breaks into the public sphere through moral panics, waves of persecution, taxonomizing projects, and medical/juridical interventions. With vivid case studies from renowned contributors, the chapters provide different theoretical approaches along with more practical examples of how to study the history of sexuality. The volume has a broad chronology from the ancient world to the present, an extensive geography covering not only Europe and the Americas but also Latin America and Africa, and also includes a variety of gender and sexual expressions. The book also privileges texts that offer an intersectional approach, asking how sex and sexualities were constructed alongside/against other categories of difference. With accessible writing, this volume encourages the reader to think creatively about how to find evidence of sex/sexuality in the past and will be of value to students as well as scholars interested in the history of sexuality.